Keefektifan ekstrak Piper retrofractum Vahl., Anonna squamosa L. dan Tephrosia vogelii Hook. serta campurannya terhadap imago kutu putih pepaya Paracoccus marginatus Williams & Granara de Willink (Hemiptera: Pseudococcidae) - Trijanti A. Widinni Asnan; Dewi Sartiami; Ruly Anwar; Dadang Dadang (Perhimpunan Entomologi Indonesia, 2015)
Paracoccus marginatus Williams & Granara de Willink (Hemiptera: Pseudococcidae) is one of the papaya insect pests that causes high economic loss. The major constraint in controling this pest with insecticides is the existence of wax layer covering the insect body.The objective of this research was to evaluate the effectiveness of Piper retrofractum (Pr), Anonna squamosa (As), and Tephrosia vogelii (Tv) extracts as well as their mixtures to control P. marginatus imago in the laboratory. Pr, As, and Tv extracts were tested separately and in extract mixtures against female P. marginatus by direct spray on the insect. Each treatment was observed at 24, 48, and 72 hours after treatment (HAT). Our result showed that at the LC95 – 72 HAT, Tv and As extracts were about three times more effective to P. marginatus than Pr extract. The effective concentration that causing around 95% mortality of P. marginatus are 1.250% (Tv), 1.482% (Pr), dan 0.469% (As). Extracts mixtures of Tv + As (2:1, w/w) and As + Ps (2 : 1, w/w) were about 1.67 times more effective than Tv + Pr (2:1, w/w) extracts mixtures. Based on combination index at 72 HST, extract mixtures of Tv + As and Tv + Pr had low sinergistic joint action, meanwhile As + Pr extract mixture had additive joint action. In addition, all the extracts treatments disturbed the formation of the wax coverings the eggs (egg sacs). Pr, As, and Tv extracts as well as their mixtures at certain extract comparison have the alternate potential to control the mealybug P. marginatus.